한국 사회에서 에이섹슈얼의 스트레스 경험과 대처 방법에 대한 합의적 질적 연구 - 안현주 (The Graduate School, Ajou University, 2024)
This study aimed to explore the stress and coping mechanisms of asexual individuals in Korean society. For this, in-depth interviews were conducted with twelve self-identified asexuals over the age of 19 who experience little or no sexual attraction. The data were analyzed using the Consensus Qualitative Research method. Our results for stressful experiences of asexual individuals revealed five domains, including ‘lack of language about identity’, ‘invisibility’, ‘ambivalent experiences caused by invisibility’, ‘misconceptions about asexual individuals’, and ‘denial of identity based on allosexuals’ perspectives’. Also, with regards to coping strategies, four domains emerged: ‘identifying as asexual’, ‘choosing not to disclose asexual identity’, ‘disclosing asexual identity’, and ‘exploring beyond asexual identity’. The findings of this study are expected to help counselors in their understanding of asexual clients. Furthermore, these findings can serve as a foundation for developing training programs for counselors who work with asexual clients.|본 연구는 한국 사회에서 에이섹슈얼이 경험하는 스트레스와 이에 대한 대처를 심층 적으로 탐색하기 위해 수행되었다. 이를 위해, 성적 끌림을 거의 또는 전혀 경험하지 않으면서 자신을 에이섹슈얼로 정체화한 만 19세 이상의 성인 12명을 대상으로 심층 면담을 진행하였고, 합의적 질적 연구 방법을 통해 자료를 분석하였다. 그 결과, 에이섹슈얼의 스트레스 경험에 대해서는 ‘정체성에 대한 언어가 부족함’, ‘눈에 띄지 않음’, ‘인식되지 않아서 편리하지만 불쾌함’, ‘에이섹슈얼에 대한 잘못된 인식’, ‘유성애자의 시선에서 나의 정체성을 재단함’이라는 5개의 영역에서 총 20개의 범주가 도출되었다. 에이섹슈얼의 스트레스 대처 방법에 대해서는 ‘에이섹슈얼로 정체화하기’, ‘드러내지 않으면서 살기’, ‘드러내면서 살기’, ‘정체성을 넘어서기’라는 4개의 영역에서 총 11개의 범주가 확인되었다. 본 연구의 결과는 에이섹슈얼 내담자에 대한 이해를 제고할 수 있도록 돕고, 더 나아가 에이섹슈얼과의 상담에 관한 교육의 기초적인 자료로 활용할 수 있을 것으로 기대된다.
학위논문(석사)--심리학과,2024. 2
Keywords: 무성애; 무성애자; 에이섹슈얼; 합의적 질적 연구